Influence of altitude on matching characteristic of electronic-controlled pneumatic two-stage turbocharging system with diesel engine. (February 2021) - Liu, Ruilin; Zhang, Zhongjie; Yang, Chunhao; Jiao, Yufei; Zhou, Guangmeng; Ma, Jiaming
Two-stage turbocharging technology is a solution to reduce turbo lag and improve the performance of engine and matching characteristics at high altitudes. In the present study, an engine testing system was established to study combustion performance and matching characteristics of a regulated two-stage turbocharging system (R2S) at different simulated altitudes. An equivalent turbocharger concept was put forward aiming to simplify the R2S with three bypass valves, and the total equivalent turbine flow area and equivalent efficiency of the R2S were obtained based on a theoretical study. Intake characteristics, combustion process, torque, power and fuel economy of the diesel engine matched with R2S were analyzed at different altitudes. The results showed that compared with 0 m, intake pressure, maximum combustion pressure, cumulative heat release, heat release rate decreased by 36.5%, 33.6%, 33.5%, 21.6%, −8.9% at 4000 r/min, and decreased by 12.3%, 2.9%, 16.4%, 8.8%, −5.4% at the speed of 2000 r/min at the altitude of 5000 m. The torque, fuel consumption and fuel consumption rate decreased by 10.1%, 5.1% and 5.4% at engine speed of 2000 r/min and by 35.7%, 27.6% and 8.9% at engine speed of 4000 r/min at 5000 m.